Internalisasi Nilai-nilai Psikologi Pendidikan Islam dalam Interaksi Guru dan Murid di SMA Integral Hidayatullah Batam - Zaman, Kamarul (JSPH : Jurnal Sosial Politik Humaniora, 2025)
Penelitian ini bertujuan untuk mendeskripsikan proses internalisasi nilai-nilai psikologi pendidikan Islam dalam interaksi guru dan murid di SMA Integral Hidayatullah Batam. Fokus penelitian terletak pada bagaimana guru menginternalisasikan nilai-nilai keislaman melalui pendekatan psikologis, serta faktor pendukung dan penghambat yang dihadapi dalam praktik sehari-hari. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data dikumpulkan melalui observasi, wawancara mendalam dengan guru dan siswa, serta dokumentasi kegiatan sekolah. Analisis data dilakukan dengan tahapan reduksi data, a This study aims to describe the process of internalizing the values of Islamic educational psychology in teacher–student interactions at SMA Integral Hidayatullah Batam. The research focuses on how teachers internalize Islamic values through psychological approaches, as well as the supporting and inhibiting factors faced in daily practices. This research employed a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews with teachers and students, and documentation of school activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the internalization of Islamic educational psychology values is manifested through teacher role modeling (uswah hasanah), habituation of worship and Islamic character, as well as emotional and spiritual guidance in both classroom and non-classroom interactions. Supporting factors include a religious school culture, family support, and teachers’ consistency as role models. Meanwhile, inhibiting factors involve students’ diverse backgrounds, the influence of digital media, and limited time for guidance. This study concludes that the internalization of Islamic educational psychology values significantly contributes to shaping students’ religious character and positive personality. The implications highlight the importance of collaboration among teachers, schools, and families in ensuring the continuity of Islamic personality development based on educational psychology principles. penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa internalisasi nilai psikologi pendidikan Islam diwujudkan melalui keteladanan guru (uswah hasanah), pembiasaan ibadah dan akhlak Islami, serta bimbingan emosional dan spiritual dalam interaksi pembelajaran maupun nonpembelajaran. Faktor pendukung internalisasi meliputi budaya sekolah yang religius, dukungan keluarga, serta peran guru yang konsisten sebagai teladan. Sementara itu, faktor penghambat ditemukan pada perbedaan latar belakang siswa, pengaruh media digital, dan keterbatasan wa This study aims to describe the process of internalizing the values of Islamic educational psychology in teacher–student interactions at SMA Integral Hidayatullah Batam. The research focuses on how teachers internalize Islamic values through psychological approaches, as well as the supporting and inhibiting factors faced in daily practices. This research employed a qualitative approach with a descriptive method. Data were collected through observations, in-depth interviews with teachers and students, and documentation of school activities. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the internalization of Islamic educational psychology values is manifested through teacher role modeling (uswah hasanah), habituation of worship and Islamic character, as well as emotional and spiritual guidance in both classroom and non-classroom interactions. Supporting factors include a religious school culture, family support, and teachers’ consistency as role models. Meanwhile, inhibiting factors involve students’ diverse backgrounds, the influence of digital media, and limited time for guidance. This study concludes that the internalization of Islamic educational psychology values significantly contributes to shaping students’ religious character and positive personality. The implications highlight the importance of collaboration among teachers, schools, and families in ensuring the continuity of Islamic personality development based on educational psychology principles. aktu pembinaan. Penelitian ini menyimpulkan bahwa internalisasi nilai-nilai psikologi pendidikan Islam memiliki kontribusi signifikan dalam membentuk karakter religius dan kepribadian positif siswa. Implikasi penelitian ini menekankan pentingnya kolaborasi antara guru, sekolah, dan keluarga dalam menjaga kesinambungan proses pembentukan kepribadian Islami yang berlandaskan psikologi pendidikan Islam.